An analysis of strategic universal accessibility implementation in Zimbabwe’s hotel sector - Mademutsa, Loice N. (Midlands State University, 2017)
While the topical areas of hospitality service provision have been systematically investigated for the general travelling public, universal accessibility to include people with disabilities has been widely ignored. This descriptive study, attempts to provide some insights into this phenomenon. An analysis of strategic universal accessibility implementation in Zimbabwe’ hotel sector was done. Self administered questionnaires and personal interviews were used to gather data from the research subjects. This article investigated how 3-5 star hotels in Harare are faring in terms of ensuring that their tourism product and services are universally accessible. The choice of hotels was based on stratified sampling technique, and simple random sampling was applied to hotels in the same strata which regarded all the graded hotels as advanced enough to respond to the global phenomenon of universal access. The choice of key stakeholders was based on purposive sampling technique as there are only limited numbers of primary data sources who are knowledgeable on universal accessibility issues. The study was approached from a pragmatism research philosophy as the research questions were both qualitative and quantitative in nature. A total of 31 hotel managers, 181 employees, and 3 key informants in the hotel sector participated in the study. Descriptive frequencies and inductive thematic data analysis were selected as the data analysis techniques for quantitative and qualitative data respectively. The research findings point to a glaring picture which calls for government intervention and business mind shift by hotel operators.